A systematic review on chlorine tolerance among bacteria and standardization of their assessment protocol in wastewater. (11th July 2022) - Gupta, Vinayak; Shekhawat, Sandeep Singh; Kulshreshtha, Niha Mohan; Gupta, Akhilendra Bhushan
Though chlorine is a cost-effective disinfectant for water and wastewaters, the bacteria surviving after chlorination pose serious public health and environmental problems. This review critically assesses the mechanism of chlorine disinfection as described by various researchers; factors affecting chlorination efficacy; and the re-growth potential of microbial contaminations in treated wastewater post chlorination to arrive at meaningful doses for ensuring health safety. Literature analysis shows procedural inconsistencies in the assessment of chlorine tolerant bacteria, making it extremely difficult to compare the tolerance characteristics of different reported tolerant bacteria. A comparison of logarithmic reduction after chlorination and the concentration-time values for prominent pathogens led to the generation of a standard protocol for the assessment of chlorine tolerance. The factors that need to be critically monitored include applied chlorine doses, contact time, determination of chlorine demands of the medium, and the consideration of bacterial counts immediately after chlorination and in post chlorinated samples (regrowth). The protocol devised here appropriately assesses the chlorine-tolerant bacteria and urges the scientific community to report the regrowth characteristics as well. This would increase the confidence in data interpretation that can provide a better understanding of chlorine tolerance in bacteria and aid in formulating strategies for effective chlorination. HIGHLIGHTS: A systematic review of chlorine tolerance studies reported on >20 pathogens performed. Mechanism of chlorination and chlorine tolerance among bacteria discussed. Lack of uniformity in chlorine tolerance studies identified as major loophole. Standardized protocol suggested to facilitate data comparability. Study expected to aid in formulating strategies for effective chlorination. Graphical Abstract